2021
DOI: 10.1016/j.ijid.2020.11.146
|View full text |Cite
|
Sign up to set email alerts
|

Nerve conduction study and electromyography findings in patients recovering from Covid-19 – Case report

Abstract: Highlights SARS-COV-2 may induce myopathy. SARS-COV-2 may induce demyelinating polyneuropathy. COVID-19 neuromusclar effects may be depicted by NCS and EMG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
5
18
1
3
Order By: Relevance
“…It is likely that CPK serum level sensitivity is lower in such a scenario. In line with our results, Daia et al have hypothesized a temporary myopathic injury without persistently elevated enzymes after SARS-Cov-2 infection [23].…”
Section: Discussionsupporting
confidence: 93%
“…It is likely that CPK serum level sensitivity is lower in such a scenario. In line with our results, Daia et al have hypothesized a temporary myopathic injury without persistently elevated enzymes after SARS-Cov-2 infection [23].…”
Section: Discussionsupporting
confidence: 93%
“…One study has reported that the neurological symptoms preceded the respiratory symptoms [12]. However, some case reports and studies showed that neuropathy started after the respiratory symptoms started resolving as in our case [4,13,14]. Nonetheless, most of the cases with these symptoms of peripheral neuropathy had prolonged intensive care stay which was not present in our case [4,7].…”
Section: Discussioncontrasting
confidence: 50%
“…This paper continues previous observations of our study group where using NCS we advanced the supposition that COVID-19 may cause polyneuropathy and myopathy. 9 …”
Section: Discussionmentioning
confidence: 99%